Hemophilia - Recent Advances 2019
DOI: 10.5772/intechopen.81429
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-Phenotype Heterogeneity in Haemophilia

Abstract: Haemophilia was previously regarded as a classical example of Mendelian inheritance, with mutation in only a single gene (F8 or F9) causing the disease phenotype. The disease manifests complete penetrance. Studies, however, revealed the striking genetic and phenotypic heterogeneities of the disease. With further sophistication of clinical and molecular techniques, the disease was also found to have allele heterogeneity, phenotypic plasticity and variation in expressivity. The variations are more pronounced in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
3
0
1
Order By: Relevance
“…Furthermore, the G allele, seen in the F9 Malmö polymorphism, c.580G > A (p.Ala 194 Thr), has a MAF of .32 38 . However, according to literature the Malmö variant has not been reported to have any association with haemophilia B 39,40 . The combined effect of this complex variant results in the amino acid change (p.Val 243 Phefs*2) within the EGF1 domain of the FIX protein.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the G allele, seen in the F9 Malmö polymorphism, c.580G > A (p.Ala 194 Thr), has a MAF of .32 38 . However, according to literature the Malmö variant has not been reported to have any association with haemophilia B 39,40 . The combined effect of this complex variant results in the amino acid change (p.Val 243 Phefs*2) within the EGF1 domain of the FIX protein.…”
Section: Discussionmentioning
confidence: 99%
“…Modifier genes and environmental factors may play a role in phenotypic heterogeneity. 4,42 Determination of the parental origin of F8 pathogenic variants in pedigrees is one of the important issues in carrier detection and PND for HA. Molecular analysis of the F8 gene combined with linkage analysis using genetic markers can be useful in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…Eugenol (1-allyl-4-hydroxy-3-methoxybenzene) is the primary ingredient of Ocimum gratissimum, a phenolic compound 9 . It has a broad therapeutic activity such as analgesic 10 , anti-inflammatory 11 , anti-bacterial 12 , anti-fungal 13 , and anti-viral 14 . It is also reported that eugenol has antioxidant activity 15 , and psoriatic patients often report redox imbalance, which implies the therapeutic potential of eugenol in psoriasis.…”
Section: Introductionmentioning
confidence: 99%